2021
DOI: 10.1039/d1cp00809a
|View full text |Cite
|
Sign up to set email alerts
|

Single-cluster electronics

Abstract: This article reviews the scope of inorganic cluster compounds measured in single-molecule junctions. The article explores how the structure and bonding of inorganic clusters give rise to specific quantum transport phenomena in molecular junctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 113 publications
0
20
0
Order By: Relevance
“…Efforts are currently underway in our laboratory to use our site‐selective functionalization strategies to probe single‐molecule conductance in sila‐adamantane‐based molecular junctions. Based on the ordering of symmetric and anti‐symmetric frontier MOs in the present DFT study, we anticipate that electronic transport in sila‐adamantane junctions will be sensitive to destructive σ‐quantum interference effects [29, 30, 74–76] …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Efforts are currently underway in our laboratory to use our site‐selective functionalization strategies to probe single‐molecule conductance in sila‐adamantane‐based molecular junctions. Based on the ordering of symmetric and anti‐symmetric frontier MOs in the present DFT study, we anticipate that electronic transport in sila‐adamantane junctions will be sensitive to destructive σ‐quantum interference effects [29, 30, 74–76] …”
Section: Discussionmentioning
confidence: 90%
“…Based on the ordering of symmetric and antisymmetric frontier MOs in the present DFT study, we anticipate that electronic transport in sila-adamantane junctions will be sensitive to destructive σ-quantum interference effects. [29,30,[74][75][76]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, calculations have shown that HOMO and HOMO−1 inversions were associated with the appearance of destructive quantum interference in permethylated oligosilanes, which occurred when the dihedral angles of the internal Si–Si–Si–Si was varied from 90° to 0°. 11 Next, transmission calculations of M3 connected to two 1D leads were carried out where site energy for nitrogen was decreased from 0 to −0.3, and the calculations revealed that the anti-resonance character of the destructive quantum interference disappeared at ε p = −0.225 or lower values (Fig. 4d).…”
Section: Control the Conductance Of π-Conjugated Molecules By Phmentioning
confidence: 97%
“…4,5 Another commonly used method for measuring single-molecule conductance is the mechanically controlled break junction (MCBJ) technique that provides benefits such as enhanced mechanical stability. 6,7 In the past decade, we have seen a growing number of organic, 8 organometallic, 9,10 inorganic cluster, 11 peptide, 12,13 and DNA 14,15 molecules being investigated for relating their single-molecule electronic properties to their structures.…”
Section: Introductionmentioning
confidence: 99%